2023
DOI: 10.1155/2023/9936114
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding Basic Life Support among Health Care Workers of the Hospital of Nepal

Abstract: Basic life support refers to a sequence of care provided to patients who are experiencing respiratory arrest, cardiac arrest, or airway obstruction. It is a specific level of prehospital medical care provided by the trained responders, including emergency medical technicians, in the absence of advanced medical care to maintain the patient’s life. BLS course trains participants to promptly recognize several life-threatening emergencies, give high-quality chest compressions, deliver appropriate ventilations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Notably, in our study, the majority of the trainers were female (67.01%). A similar trend was observed in an Indian study examining healthcare workers' familiarity with CPR knowledge and skills [11]. Nevertheless, our current study's results demonstrated no significant gender-based disparities in BLS knowledge accuracy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, in our study, the majority of the trainers were female (67.01%). A similar trend was observed in an Indian study examining healthcare workers' familiarity with CPR knowledge and skills [11]. Nevertheless, our current study's results demonstrated no significant gender-based disparities in BLS knowledge accuracy.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, more than half of the trainees had a bachelor degree (257 (66.75%)), followed by master's degree holders (96 (24.94%)), college degree holders (29 (7.53%)), and doctoral degree holders (3 (0.78%)). Using educational attainment as the independent variable, our study showed that there was no correlation between the accuracy of BLS knowledge and educational attainment, similar to researchers in Nepal who investigated the BLS knowledge of health care workers [11,12]. Regarding work experience, our study revealed that the majority, 79.74%, had 0-1 year of experience, followed by 10.39% with 2-3 years, 6.23% with more than 6 years, and 3.64% with 4-5 years of experience.…”
Section: Discussionsupporting
confidence: 84%
“…This study, set against the backdrop of a city that attracts a substantial patient population from peripheral areas, underscores the critical need for healthcare professionals to possess robust BLS skills and knowledge. The significant knowledge and practice discrepancies observed in CPR and AED usage among participants echo findings from various international studies, highlighting a global challenge within healthcare education and practice (5,17). The analysis revealed that a considerable portion of both doctors and nurses lacked essential knowledge and practical skills in BLS, akin to observations in studies from India and Pakistan (12).…”
Section: Discussionsupporting
confidence: 51%
“…Although the degree of training and proficiency in basic life support differs between healthcare workers and hotel staff, the knowledge of hotel staff was found to be higher than that of healthcare workers. A study found that only 12% of healthcare workers had adequate knowledge of basic life support (Chaudhary et al, 2023). Most healthcare workers, especially nurses, require improvement in their knowledge of basic life support (Adal & Emishaw, 2023).…”
Section: Discussionmentioning
confidence: 99%